An investigation of p53’s differential activation of cell cycle arrest and apoptosis - Zhang, Yuan (Curtin University, 2008)
The p53 tumour suppressor protein lies at the hub of a very complex network of cellular pathways including apoptosis, cell cycle arrest, DNA repair and cellular senescence. However, the mechanism of why and how p53 switches between apoptosis and cell cycle arrest, thereby determining a cell’s fate, remains a mystery to us. To enable us to investigate this ability of p53 to switch between cell cycle arrest and apoptosis, we developed a model which demonstrates similar p53 expression patterns but different functional outcomes. Treating cells with Cisplatin (a common chemotherapeutic drug) and Nutlin-3 (an MDM-2 inhibitor) results in similar high levels of p53 accumulation but different cellular responses. Cisplatin-treated cells undergo apoptosis while Nutlin-treated cells enter cell cycle arrest. Using this model, we explored the localization of p53 and in particular a C-terminal Ser 392 moiety in an attempt to identify how p53 is able to preferentially activate cell cycle arrest or apoptotic pathway.